Unitary equivalence of multiplication operators on the Bergman spaces of polygons. Issue 1 (5th March 2022) - Huang, Hansong; Zheng, Dechao
Abstract: In this paper, we will show that the unitary equivalence of two multiplication operators on the Bergman spaces on polygons depends on the geometry of the polygon.